2022
DOI: 10.1177/00033197221130571
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Venous Insufficiency in A Selected Nurse Population: A Cross-Sectional Study

Abstract: Chronic venous insufficiency (CVI) causes severe symptoms and complications in the general population, but the prevalence, related risk factors, and treatment of CVI are unknown among nurses. The demographics and occupational factors of nurses from a university hospital were collected by questionnaires, and the presentation of CVI was confirmed by the specialist vascular surgeons. A total of 1606 participants were enrolled, and the prevalence of CVI was 7.5%. After multivariate adjustment, CVI was positively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…46 Furthermore, this effect seems to be dependent on increased standing time and increased time in night shift rotation. 47 Another study including hair dressers showed similar results. 48 Overweight (body mass index: 25.0-29.9 kg/m 2 ) and obesity (body mass index !…”
Section: Pathophysiologymentioning
confidence: 68%
See 2 more Smart Citations
“…46 Furthermore, this effect seems to be dependent on increased standing time and increased time in night shift rotation. 47 Another study including hair dressers showed similar results. 48 Overweight (body mass index: 25.0-29.9 kg/m 2 ) and obesity (body mass index !…”
Section: Pathophysiologymentioning
confidence: 68%
“…7,41 Regarding oral contraceptives, a recent study revealed an association between their use and a decreased risk of chronic venous insufficiency. 42 When analyzing hemostatic factors among patients participating in the Edinburgh Vein Study, elevated levels of fibrinogen, tissue plasminogen activator, and von Willebrand factor were observed in individuals with trunk varicose veins and chronic venous insufficiency. However, upon adjusting for confounding factors, these associations were attenuated.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the prevalence of CVD globally increased from 7.5% to 73% varied by gender, aging, geographic area, and occupational factors ( Saliba et al, 2020 ; Aslam et al, 2022 ; Gujja et al, 2022 ; Stücker and Rabe, 2022 ). Compression therapeutic textiles (CTs)—as the traditional intervention modalities—are extensively applied for the medical treatment and prevention of chronic leg ulcers in physical-based compression therapy ( Stücker et al, 2020 ; Mestre et al, 2022 ; Xiang et al, 2022 ). By varying material stiffness, gradient external compressions distributed by elastic knitted CTs could reduce venous wall distension and promote venous hemodynamics from the distal to the proximal regions of lower extremities ( Orhurhu et al, 2021 ; Raffetto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%